Developing Specialized Court Services : International Experiences and Lessons Learned - Gramckow, Heike (World Bank, Washington, DC, 2014)
Court specialization is commonly considered to be an important reform initiative to advance the development of a successful judicial system. Court specialization is thought useful even to address broader development constraints, such as the need for more effective access to contract enforcement, improvements in the investment climate, or more adequate protection of the environment. These studies have also pointed to some drawbacks, however. For example, special attention to, and the allocation of additional resources for, handling business cases can lead to the perception that a court provides preferential services to the business community but not the average person. Judges may also develop too close a relationship with a particular group of lawyers and interest groups that are involved in special case types, especially if those groups are relatively small and if judges serve in this special capacity exclusively and for an extended period. This report outlines the international experiences and good practices related to establishing specialized courts and creating the associated judicial expertise. It specifically highlights the information that is needed to determine if specialization is required in particular areas, as well as the specialization model that may be most appropriate, the requirements of the different models, and the approaches to training and selecting judges for special assignments. The paper also outlines the next steps a jurisdiction might take to examine the potential need and demand for further specialized judicial services and to consider what would be needed to meet those which are justified.